Leaf shape simulation of castor bean and its application in nondestructive leaf area estimation - Wei, Hailin; Li, Xumeng; Li, Ming; Huang, Huang (International Journal of Agricultural and Biological Engineering, 2019)
The leaf shape and leaf area measurement are crucial in plant growth modeling. The castor bean leaf is large, palm-shaped with multiple clefts. The leaf shape simulation and leaf area estimation were less studied. The circular model and nonrectangular hyperbolic model were developed to describe the standard leaf shape of castor bean in this study, providing a model for simulating the leaf shape and a nondestructive way for estimating the leaf area respectively. In addition, a formula was established to estimate the leaf area by the parameter of the standard leaf shape of castor bean. Based on validation results, the circular model fits the landmarks and nonrectangular hyperbolic model fits the lobe margins very well. The leaf area was accurately estimated by using the established formula. This study could provide a theoretical reference for leaf visualization, a nondestructive and easy way to estimate the leaf area for other complex leaves with multiple lobes.Keywords: leaf shape, leaf area, geometrical characteristics, mathematical model, image processing, plant growth modelingDOI: 10.25165/j.ijabe.20191204.4040Citation: Wei H L, Li X M, Li M, Huang H. Leaf shape simulation of castor bean and its application in nondestructive leaf area estimation. Int J Agric & Biol Eng, 2019; 12(4): 135–140.